Dynamic Relation of Changes in Weight and Indices of Fat Distribution With Cardiac Structure and Function: The Dallas Heart Study. Issue 7 (July 2017) - Wilner, Bryan; Garg, Sonia; Ayers, Colby R.; Maroules, Christopher D.; McColl, Roderick; Matulevicius, Susan A.; de Lemos, James A.; Drazner, Mark H.; Peshock, Ronald; Neeland, Ian J.
Abstract : Background: Obesity may increase heart failure risk through cardiac remodeling. Cross‐sectional associations between adiposity and cardiac structure and function have been elucidated, but the impact of longitudinal changes in adiposity on cardiac remodeling is less well understood. Methods and Results: Participants in the Dallas Heart Study without cardiovascular disease or left ventricular dysfunction underwent assessment of body weight, anthropometrics, and cardiac magnetic resonance imaging at baseline and 7 years later. Associations between changes in indices of generalized and central adiposity with changes in left ventricular mass, volume, mass/volume ratio (concentricity), wall thickness, and ejection fraction were assessed using multivariable linear regression. The study cohort (n=1262) mean age was 44 years with 57% women, 44% black, and 36% obese participants. At follow‐up, 41% had ≥5% weight gain, and 15% had ≥5% weight loss. Greater weight gain was associated with younger age, lower risk factor burden, and lower body mass index at baseline. In multivariable models adjusting for age, sex, race, comorbid conditions at baseline and follow‐up, baseline adiposity, and cardiac measurement, increasing weight was associated with increases in left ventricular mass (β=0.10, P <0.0001), wall thickness (β=0.10, P <0.0001), and concentricity (β=0.06, P =0.002), with modest effects on end‐diastolic volume (β=0.04, P =0.044) and ejection fraction (β=0.05, P =0.046). Similar results were seen with other adiposity indices. Conclusions: Concentric left ventricular remodeling is the predominant phenotype linked to increasing adiposity in middle age. Our findings support the importance of weight management to prevent secular changes in adiposity, concentric remodeling, and eventual heart failure over time.